2015
DOI: 10.1111/jfq.12154
|View full text |Cite
|
Sign up to set email alerts
|

Ultrasonic‐Assisted Solvent Extraction of Carotenoids From Rapeseed Meal: Optimization Using Response Surface Methodology

Abstract: Ultrasound-assisted solvent extraction of carotenoids from rapeseed meal was investigated and evaluated by response surface methodology. We have compared the yields of carotenoids by using five different solvent systems, and found that the highest yield can be achieved under petroleum ether/acetone (v/v = 1/1). We have further tested the effect of ultrasonic power, modulation frequency, duration, temperature, liquid to material ratio and extraction times on the yield of carotenoids by adopting Plackett-Burman … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

4
11
0

Year Published

2016
2016
2022
2022

Publication Types

Select...
4
4
1

Relationship

0
9

Authors

Journals

citations
Cited by 32 publications
(15 citation statements)
references
References 31 publications
4
11
0
Order By: Relevance
“…According to the experimental design and results in Table 1 Analysis of variance (ANDVA) in Table 2 showed that the determination coefficient (R 2 ) and the adjusted determination coefficient (R2 adj) were 0.9864 and 0.9619, respectively. These results showed the model was properly interpreted for the test data (Deng et al, 2016) and the data were good in agreement with the predicted values (Yan et al, 2016). The model for the yield was highly significant for the p-value (0.0004) that was less than 0.05.…”
Section: Model Fitting and Effect Analysessupporting
confidence: 56%
“…According to the experimental design and results in Table 1 Analysis of variance (ANDVA) in Table 2 showed that the determination coefficient (R 2 ) and the adjusted determination coefficient (R2 adj) were 0.9864 and 0.9619, respectively. These results showed the model was properly interpreted for the test data (Deng et al, 2016) and the data were good in agreement with the predicted values (Yan et al, 2016). The model for the yield was highly significant for the p-value (0.0004) that was less than 0.05.…”
Section: Model Fitting and Effect Analysessupporting
confidence: 56%
“…With these optimized conditions, the predicted response for carotenoid yield was approximately 0.1570 mg/g, and the experimental value was found as 0.1577 ± 0.0014 mg/g. These results confirmed that experimental values are in agreement with the predicted values, thus the model was validated [31].…”
Section: Validation Of the Modelsupporting
confidence: 80%
“…As shown in Table 3, the determination coefficient (R 2 ) is 0.9865 which indicates that the model is a reasonable fit for the experimental data (Deng et al, 2016;Han et al, 2016) and the adjusted determination coefficient (R2 adj) is 0.9865 which means the experimental results are highly consistent with the predicted values (Han et al, 2016;Yan et al, 2016). Moreover, the model p-value is 0.0004, which indicates that the regression model is highly significant.…”
Section: Model Fittingmentioning
confidence: 72%